Antipsychotic plasma levels in the assessment of poor treatment response in schizophrenia. (26th October 2017) - McCutcheon, R.; Beck, K.; D'Ambrosio, E.; Donocik, J.; Gobjila, C.; Jauhar, S.; Kaar, S.; Pillinger, T.; Reis Marques, T.; Rogdaki, M.; Howes, O. D.
Abstract : Objective: Treatment resistance is a challenge for the management of schizophrenia. It is not always clear whether inadequate response is secondary to medication ineffectiveness, as opposed to medication underexposure due to non‐adherence or pharmacokinetic factors. We investigated the prevalence of subtherapeutic antipsychotic plasma levels in patients identified as treatment‐resistant by their treating clinician. Method: Between January 2012 and April 2017, antipsychotic plasma levels were measured in 99 individuals provisionally diagnosed with treatment‐resistant schizophrenia by their treating clinicians, but not prescribed clozapine. Patients were followed up to determine whether they were subsequently admitted to hospital. Results: Thirty‐five per cent of plasma levels were subtherapeutic, and of these, 34% were undetectable. Black ethnicity ( P  = 0.006) and lower dose ( P  < 0.001) were significantly associated with subtherapeutic/undetectable plasma levels. Individuals with subtherapeutic/undetectable levels were significantly more likely to be admitted to hospital ( P  = 0.02). Conclusion: A significant proportion of patients considered treatment‐resistant have subtherapeutic antipsychotic plasma levels, and this is associated with subsequent admission. The presence of subtherapeutic plasma levels may suggest a need to address adherence or pharmacokinetic factors as opposed to commencing clozapine treatment. While antipsychotic levels are not recommended for the routine adjustment of dosing, they may assist with the assessment of potential treatment resistance in schizophrenia.